Can the reductive dissolution of ferric iron in paddy soils compensate phosphorus limitation of rice plants and microorganisms?. (May 2022) - Wang, Chaoqun; Thielemann, Lukas; Dippold, Michaela A.; Guggenberger, Georg; Kuzyakov, Yakov; Banfield, Callum C.; Ge, Tida; Guenther, Stephanie; Bork, Patrick; Horn, Marcus A.; Dorodnikov, Maxim
Abstract: Biogeochemical cycles of phosphorus (P) and iron (Fe) are tightly interlinked, especially in highly weathered acidic subtropical and tropical soils rich in iron (oxyhydr)oxides (Fe(III)). The quantitative contribution of the reductive dissolution of Fe(III)-bound inorganic P (Pi ) (Fe–P) in low-redox paddy soils may cover the demands of rice plants ( Oryza sativa L.) and microorganisms. We hypothesized that microbially-driven Fe(III) reduction and dissolution can cover the P demand of microorganisms but not of the young rice plants when the plants' P demand is high but their root systems are not sufficiently developed. We grew pre-germinated rice plants for 33 days in flooded rhizoboxes filled with a paddy soil of low P availability. 32 P-labeled ferrihydrite (30.8 mg kg −1 ) was supplied either (1) in polyamide mesh bags (30 μm mesh size) to prevent roots from directly mobilizing Fe–P (pellets-in-mesh bag treatment), or (2) in the same pellet form but without a mesh bag to enable roots accessing the Fe–P (pellets-no-mesh bag treatment). Without mesh bags, Pi was more available leading to increases in microbial biomass carbon (MBC) by 18–55% and nitrogen (MBN) by 4–108% in rooted soil as compared to Pi pellets not directly available to roots. The maximum enzyme activities (Vmax ) of phosphomonoesterase and β-glucosidase followed this pattern. During rice root growth, day 10 to day 33, MBC and microbial biomass phosphorus (MBP) contents in both rooted and bottom bulk (15–18 cm) soil gradually decreased by 28–56% and 47–49%, respectively. In contrast to our hypothesis, the contribution of Fe–P to MBP remarkably decreased from 4.5% to almost zero from 10 to 33 days after rice transplantation, while Fe–P compensated up to 16% of the plant P uptake at 33 days after rice transplantation, thus outcompeting microorganisms. Although both plants and microorganisms obtained Pi released by Fe(III) reductive dissolution, this mechanism was not sufficient for the demand of either organism groups. Graphical abstract: Image 1 Highlights: 32 P application can assess plant-microbial competitive dynamics for P absorbed by Fe. Contribution of Fe–P to MBP decreased from 4.5% to almost zero with rice growth. Fe–P compensated up to 16% of rice P uptake during 33 days after rice transplantation. Rice plants outcompeted microorganisms for P at the tillering stage.